ANALISIS PERBANDINGAN KINERJA KEUANGANBANK SYARIAH DENGAN MENGGUNAKAN PENDEKATAN LABA RUGI (INCOMESTATEMENT APPROACH) DAN NILAI TAMBAH(VALUE ADDED STATEMENT) PERIODE 2011-2014 - admin, FEBI ALPIANITA B11111158 (Jurnal Manajemen Update, 2016)
Abstract: The purpose of this research to analysis whether there are significant differences of Islamic banking financial statements using the income statement approach and value added statement is measured using financial ratios. Financial ratios used in this study is LBAP,ROA ,ROE , and NPM. Objects used in this study is the financial statements have been audited by an independent auditor in the period 2011 - 2014 of Bank Syariah Mandiri , Bank Muamalat Indonesia Syariah , Bank  BCA Syariah , Bank BRI Syariah , Bank Bukopin Syariah, Bank Mega Syariah, Bank Panin Syariah and the BNI Syariah using two approaches is income statement approach and value added statement . The analytical tool used in this study is two related samples test (Uji Wilcoxon) with SPSS 16.00 for Windows. The results of this study indicate that the ratio of LBAP ROA , ROE , and NPM has a significant difference between the income statement approach and value added statement. While the overall performance showed that profabilitas contained significant levels of each difference between the income statement approach and value added statement. Keywords : Financial Performance, Islamic Banking, Income, Value Added, Enterprise Sharia Theory (SET) , LBAP, ROA , ROE ,  NPM